The Analysis of Women's Choices in Hopeless by Colleen Hoover - Nabila, Aura Safa; Supiastutik (Lakon : Jurnal Kajian Sastra dan Budaya, 2024)
This study delves into how women's choices are represented through a sexual abuse survivor character in Colleen Hoover's novel Hopeless. The novel addresses the issue of women's choices, depicted by two main female characters who have experienced sexual abuse by their family members. This research uses representation theory and a postfeminist perspective to analyze this portrayal of women's choices. This research identifies three choice categories for sexual abuse survivors striving for happiness: 1) women decide what they want, 2) women dare to take risks, and 3) women choose to self-acceptance. The two main female characters in Hopeless are portrayed as courageous individuals who dare to break away from the victim label by making bold and meaningful choices.